Development of E-Modules Based on Problem Based Learning (PBL) on the Circulatory System Material for Grade XI Senior High School to Improve Critical and Collaborative Thinking Skills - Megawati; Fitri Arsih; Lufri; Elsa Yunuarti (Postgraduate, University of Mataram, 2026)
21st century education demands students to have critical thinking and collaboration skills. However, observations in class XI of SMAN 2 Sungai Penuh revealed low levels of these skills due to the lack of relevant learning media. Therefore, PBL-based E-modules are needed. This study aims to produce a valid, practical, and effective PBL-based E-module on the circulatory system material. This research employed Research and Development (R&D) using the ADDIE model, combined with a Quasi-Experimental Design (Pretest-Posttest Control Group Design) for effectiveness testing. The research subjects were 72 eleventh-grade students of SMAN 2 Sungai Penuh, divided into an experimental class (n = 36) and a control class (n = 36), selected through cluster random sampling. Instruments included validation sheets, practicality questionnaires, critical thinking tests, and collaboration observation sheets. Data analysis used descriptive statistics for validity and practicality, while effectiveness was analyzed using N-Gain scores and Independent Sample T-Test with SPSS 26 at α=0.05. Results showed validity of 95.49% (very valid), teacher practicality of 100% and student practicality of 92.89% (very practical). Effectiveness analysis revealed significant differences between groups (t= 4.523, p < 0.001) with experimental class N-Gain of 0.72 (high) compared to control class N-Gain of 0.45 (medium). Thus, the PBL-based E-module is valid, practical, and effective in improving students' critical thinking and collaboration skills.